From Periphery to Core: Economic Adjustments to High Speed Rail. - Ahlfeldt, Gabriel M.; Feddersen, Arne (My University, 2010)
This paper presents evidence that high speed rail systems sustainably promote economic activity within regions that enjoy an increase in accessibility. Our results one the one hand confirm expectations that have led to huge public investments into high speed rail all over the world, suggesting that these investments are economically viable. On the other hand, our results confirm theoretical predictions arising from a consolidate body of (New) Economic Geography literature taking a positive, man-made and reproducible shock as a case. We argue that the economic geography framework can help to derive ex-ante expectations on the economic impact of transport projects. The subject case is the German high speed rail track connecting Cologne and Frankfurt, which, provides exogenous variation in access to regions due to the construction of intermediate stations in the towns of Limburg and Montabaur.
Keywords: Verkehr; Verkehrsplanung; Schienenverkehr; Verkehrspolitik; Verkehrsökonomie